A concise guide to macroeconomics : what managers, executives, and students need to know - Moss, David A. , 1964- (Harvard Business School Press, 2007)
Presenting macroeconomic concepts, this book introduces tools for interpreting the big-picture economic developments that shape events in the contemporary business arena. It includes examples which are drawn from history to illuminate useful concepts